Methods Of Making Tongues Of Fire To Be Tied On The Ends Of Lances Like Squibs. (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1942)
IN order to defend batteries or to make a stratagem at night in making an assault it is useful to tie certain tubes of paper on wooden forms to the ends of the lances of the cavalry, or on the ends of the pikes of infantrymen. These are made in the form , of rockets or squibs, half a braccio or more long, and are full of coarse gunpowder in which are mixed pieces of Grecian pitch, sulphur, grains of common salt, iron filings, crushed glass, crystalline arsenic, and the like. Their very shape gives a hold at the foot, and they should be well packed and full. Then, having put in a good fuse and turned the fire-emitting end toward the enemy and having tied it well to the lance or pike, at the proper time cause them to burn as you wish. From the thing made in this way you will see issue a fearful very hot tongue of fire more than two braccia long, full of explosions and horror. This works much better if used when the weather is mild or when you are aided by the wind. This thing serves very well in battles at sea as well as in its effects on land.